The average rate of change over is 1
Explanation:
Given that the function is [tex]G(t)=-(t-1)^2+5[/tex]
We need to determine the average rate of change over the interval [tex]-4\leq t\leq 5[/tex]
The value of G(-4):
The value of G(-4) can be determined by substituting t = -4 in the function [tex]G(t)=-(t-1)^2+5[/tex]
Thus, we have,
[tex]G(-4)=-(-4-1)^2+5[/tex]
[tex]G(-4)=-(-5)^2+5[/tex]
[tex]G(-4)=-(25)+5[/tex]
[tex]G(-4)=-20[/tex]
Thus, the value of G(-4) = -20
The value of G(5):
The value of G(5) can be determined by substituting t = 5 in the function [tex]G(t)=-(t-1)^2+5[/tex], we get,
[tex]G(5)=-(5-1)^2+5[/tex]
[tex]G(5)=-(4)^2+5[/tex]
[tex]G(5)=-16+5[/tex]
[tex]G(5)=-11[/tex]
Thus, the value of G(5) is -11
Average rate of change:
The average rate of change can be determined using the formula,
[tex]\frac{G(b)-G(a)}{b-a}[/tex]
where [tex]a=-4[/tex] and [tex]b=5[/tex]
Substituting the values, we get,
[tex]\frac{G(5)-G(-4)}{5-(-4)}[/tex]
Substituting [tex]G(5)=-11[/tex] and [tex]G(-4)=-20[/tex], we get,
[tex]\frac{-11+20}{5+4}[/tex]
[tex]\frac{9}{9}=1[/tex]
Thus, the average rate of change over the interval [tex]-4\leq t\leq 5[/tex] is 1.